Port integration in global supply chains: measures and implications for maritime logistics - Song, Dongwook; Panayides, Photis (My University, 2009)
The aim of this article is to define and empirically develop measures of seaport integration in global supply chains and to infer implications for maritime logistics. A literature review identified four key parameters hypothesised to be part of the higher-order construct of 'terminal supply chain integration' (TESCI). Data for operationalizing the conceptualised variables were obtained via a large scale survey of container terminal operators. A model was developed and validated using confirmatory factor analysis. The validated parameters of the higher-order construct of 'TESCI' included 'information and communication systems', 'value-added services', 'multimodal systems and operations', and 'supply chain integration practices'. The study provides implications for maritime logistics by focusing on key parameters such as determination of costs, revenues, performance, productivity, and competitive advantage for international supply chains
Keywords: Ports; Maritime logistics; Supply chain integration